Relación entre ansiedad y conductas agresivas en adolescentes que cursan el Décimo Año de Educación Básica de la Unidad Educativa Adolfo Valarezo, periodo 2018 - 2019 - González Torres, Byron Agustín (2019)
Adolescence is a stage that is full of changes, in this period of human life can be presented factors that alter the same, it is for the reason that in adolescence can have different life crises which can lead to produce anxiety and this trigger aggressive behavior. For the above mentioned and seeing that this reality is no stranger in our midst, came the need for research work called, relationship between anxiety and aggressive behavior in adolescents enrolled in the tenth year of basic education Educational Unit Adolfo Valarezo, 2018-2019 period, the same as determine the relationship between levels of anxiety and aggressive behavior. The sample was 154 respondents, 98 females and 56 males in aged from 13 to 17 years. He studio was descriptive, quantitative, prospective and correlational. For data collection and analysis thereof, it was usedandl informed consent, Inventory Situations and Responses Anxiety ISRA-J, the Aggression Questionnaire Reactive-Proactive (RPQ), SPSS version 25 and the correlation coefficient Spearman's Rho, showing in adolescent’s positive relationship between levels of anxiety and aggression, which proves the correlation between variables indicating that high levels of anxiety aggressive behaviors are presented. 48% showed severe anxiety and aggression cognitive response reactive 43% moderate level. KEYWORDS: Adolescence, Anxiety and aggression.